2023
DOI: 10.3390/v15091872
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Antiviral Activity of Influenza A Defective Interfering Particles against Respiratory Syncytial, Yellow Fever, and Zika Virus Replication In Vitro

Lars Pelz,
Elena Piagnani,
Patrick Marsall
et al.

Abstract: New broadly acting and readily available antiviral agents are needed to combat existing and emerging viruses. Defective interfering particles (DIPs) of influenza A virus (IAV) are regarded as promising options for the prevention and treatment of IAV infections. Interestingly, IAV DIPs also inhibit unrelated viral infections by stimulating antiviral innate immunity. Here, we tested the ability of IAV DIPs to suppress respiratory syncytial, yellow fever and Zika virus infections in vitro. In human lung (A549) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 95 publications
(186 reference statements)
0
4
0
Order By: Relevance
“…For instance, mice were rescued from a lethal dose of influenza B virus and pneumonia virus of mice by DIP co-administration 38 , 41 . In addition, we demonstrated a pronounced antiviral effect against SARS-CoV-2 37 and against respiratory syncytial, yellow fever and Zika virus replication in vitro 42 . Such broad protective immunity against many different unrelated viruses was also observed for dengue and poliovirus DIPs 24 , 56 .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…For instance, mice were rescued from a lethal dose of influenza B virus and pneumonia virus of mice by DIP co-administration 38 , 41 . In addition, we demonstrated a pronounced antiviral effect against SARS-CoV-2 37 and against respiratory syncytial, yellow fever and Zika virus replication in vitro 42 . Such broad protective immunity against many different unrelated viruses was also observed for dengue and poliovirus DIPs 24 , 56 .…”
Section: Discussionmentioning
confidence: 75%
“…DIP co-infections also result in a strong induction of the interferon (IFN) system 35 38 , and it was shown that this stimulation of the innate immunity also contributes to their antiviral effect 25 , 26 , 35 , 37 . As a consequence, IAV DIPs display a broad-spectrum antiviral activity that is not only directed against a wide range of IAV strains 16 , 21 , 25 , 39 , 40 , but even against unrelated viruses, including SARS-CoV-2 37 , 38 , 41 , 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Deletion DVGs identified from dengue ( Flaviviridae ), Sindbis ( Togaviridae ), and influenza virus ( Orthomyxovidae ) DIPs all showed potent IFN stimulation ( 105 107 ). One engineered deletion DVG from poliovirus ( Picornaviridae ) also induced strong IFN responses ( 108 ).…”
Section: Functions Of Dvgs/dipsmentioning
confidence: 99%
“…Simultaneously, they strongly stimulate the interferon (IFN)-induced antiviral activity against IAV infections (Frensing et al 2014 ; Huo et al 2020 ; Penn et al 2022 ). Furthermore, this unspecific innate immune response stimulation can also suppress replication of unrelated viruses including severe acute respiratory syndrome coronavirus (SARS-CoV-2) (Easton et al 2011 ; Pelz et al 2023 ; Rand et al 2021 ; Scott et al 2011 ). Previously, we discovered a new type of IAV DIP named “OP7”.…”
Section: Introductionmentioning
confidence: 99%